Pengembangan Media Pembelajaran Berbasis Aplikasi Kinemaster Untuk Menunjang Belajar Mengajar Siswa Pada Gugus 6 Pirus Martapura - Finki Dona Marleny; Ayu Ahadi Ningrum; Windarsyah Windarsyah (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2021)
Alteration in learning styles during the Covid-19 pandemic requires educators, i.e. teachers, to be more innovative in delivering learning materials so that students can understand learning materials well during learning from home. As an educator must quickly relate to these circumstances, innovation and creativity of an educator become the spearhead in the teaching and learning process so that students always feel the existence of effective interaction and communication in the teaching and learning process. Kinemaster application is one of the media that can be used to develop learning media to make it more interesting and interactive. The use of this Kinemaster application tends to be easier to implement because it is more popular and easy to use. The purpose of this community service activity is to foster the spirit of teachers and students in the teaching and learning process, as well as improve the teacher's ability to create learning media in the form of video learning materials. This community service activity took place in Group 6 Turquoise Martapura City Banjar Banjar District of South Kalimantan Province. This activity was held in August 2021 with a total of approximately 30 teachers. The method of approaching the implementation of community service activities in the form of socialization, training, and application of Kinemaster applications to create interactive learning media, beyond this activity is the improvement of teachers' in the creation and development of interactive and innovative learning media.